A multi-national survey of experience and attitudes towards commencing home parenteral nutrition for patients with advanced cancer. (February 2022) - Naghibi, M.; Skinner, C.; Burden, S.T.; Bozzetti, F.; Cuerda, C.; Joly, F.; Jeppesen, P.; Lamprecht, G.; Mundi, M.; Szczepanek, K.; Van Gossum, A.; Wanten, G.; et al.
Summary: Introduction: Advanced cancer (AC) is increasingly an indication for home parenteral nutrition (HPN) but an area with possible variation in practice between geographical locations. The aims of this study are to explore the views and experiences of international multi-disciplinary teams to determine opinions and practices. Methods: An online questionnaire was developed with members of the Home Artificial Nutrition and Chronic Intestinal Failure interest group of the European Society for Clinical Nutrition and Metabolism (ESPEN) and distributed to colleagues involved in managing patients with AC on HPN. Results: A total of 220 responses were included from 5 continents including 36 countries, with 90% of all responses from Europe. Predicted survival was a key factor influencing the decision to commence HPN for most respondents 152/220 (75%), with the majority of participants reporting that patients should have a predicted survival of ≥3 months if considered for HPN (≥3 months: n = 124, 56% vs. <3 months: n = 47, 21%, p < 0.001). However, most respondents were not confident about predicting overall survival in more than 50% of cases (confident n = 40, 23% vs not confident n = 135, 77%, p < 0.001). Barriers to utilising HPN in AC included colleagues' objections (n = 91, 46%), lack of local expertise (n = 55, 28%) and funding restrictions (n = 34, 17%). Conclusions: Significant consensus was observed regarding AC as indication for HPN, while areas of variation exist. Survival prognostication is often used as an indication for commencing HPN in people with AC, although the majority of respondents were not confident in prognosticating, suggesting better clinical prognostication tools will be of assistance. Further studies are also required to better understand the obstacles faced by clinical teams to commencing HPN that may explain variations in clinical practice between countries, as well as adressing variation in funding.